A human-machine interface design for direct rehabilitation using a rehabilitation robot - (:unkn) unknown (My University, 2008)
During the physical rehabilitation various problems are of concern for a patient. The most important difficulties, accessibility, costs, and exercise duration, are troublesome and require patience for both physiotherapist (PT) and patient. This is the main reason that is speeding up research and development of robotic rehabilitation approaches. In this study, a human machine interface has been designed for controlling of a rehabilitation robot that can perform active and passive exercises for lower limbs. Also the rehabilitation system that consists of human machine interface and robot manipulator can learn PT manual exercises and perform them by itself like a PT. So, PT rehabilitation capability is conveyed to the patient directly. The human-machine interface includes an easy-to-use graphical user interface. With this interface, the treatment period can be observed and recorded. Furthermore, the interface has been designed to be fit for web-based remote therapy. Test results of this study are to be presented for direct rehabilitation of knee and hip. Copyright 2008 ACM.
Keywords: Direct rehabilitation; Human-machine interaction; Human-machine interface; Rehabilitation robots